Adjustments to the Traditional Government System in the Muslim Malay Community of Bungo (1979–2023) - Arvionita, Diah; Hidayat, Ahmad Taufik; Hakim, Lukmanul (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This research is motivated by the changes that occurred in the customary government that survived for many years as social control in Malay society. The purpose of this research is to describe the changes in the customary government system in the muara bungo Islamic Malay community (1979-2023). The research method used is the four stages of historical research methodology, namely heuristics, source criticism, interpretation, and writing. The data collection techniques used are observation, interviews, literature study, and documentation. The results showed that as a social controller in the Malay customary society of Muara Bungo, which lost its role thanks to Law No. 5 of 1979 which changed all the smallest units into village governments. The customary government then disappeared and all the rules and customary devices that had existed after so long. This change then did not bring changes towards progress in the indigenous Malay community of Muara Bungo, it became a setback for the community. The village government only regulates village administration, not regulating the problems that arise in indigenous peoples. The loss of the Customary Chief (Pasirah) made the Malay indigenous community lose guidance, so that community problems could not be resolved by the village government. The increasingly worrying situation made the Jambi Level I regional government move by issuing Regional Regulation No. 5 of 2007 with the intention of restoring the identity, function and role of customary institutions to the community. Rio emerged as the new customary head, to socialize and teach the community the customary rules, and to peacefully resolve customary problems that occurred in the community.